AMPK blocks starvation-inducible transgenerational defects in Caenorhabditis elegans - Demoinet, Emilie (Proc Natl Acad Sci U S A, 2017)
Life history events, such as traumatic stress, illness, or starvation, can influence us through molecular changes that are recorded in a pattern of characteristic chromatin modifications. These modifications are often associated with adaptive adjustments in gene expression that can persist throughout the lifetime of the organism, or even span multiple generations. Although these adaptations may confer some selective advantage, if they are not appropriately regulated they can also be maladaptive in a context-dependent manner. We show here that during periods of acute starvation in Caenorhabditis elegans larvae, the master metabolic regulator AMP-activated protein kinase (AMPK) plays a critical role in blocking modifications to the chromatin landscape. This ensures that gene expression remains inactive in the germ-line precursors during adverse conditions. In its absence, critical chromatin modifications occur in the primordial germ cells (PGCs) of emergent starved L1 larvae that correlate with compromised reproductive fitness of the generation that experienced the stress, but also in the subsequent generations that never experienced the initial event. Our findings suggest that AMPK regulates the activity of the chromatin modifying COMPASS complex (complex proteins associated with Set1) to ensure that chromatin marks are not established until nutrient/energy contingencies are satisfied. Our study provides molecular insight that links metabolic adaptation to transgenerational epigenetic modification in response to acute periods of starvation.